Antithrombotic management for Impella® temporary ventricular assist devices: An analysis of an academic health-system experience. Issue 6 (June 2022) - Iskaros, Olivia; Ahuja, Tania; Arnouk, Serena; Toy, Bridget; Lewis, Tyler; Altshuler, Diana; Smith, Deane; Papadopoulos, John; Merchan, Cristian
The use of acute mechanical circulatory support (MCS) has increased over the last decade. For patients with left-ventricular failure, an Impella ® (Abiomed, Danvers, MA) may be used to improve cardiac output. The purpose of this study is to describe Impella ® anticoagulation patterns and evaluate the safety and effectiveness of our protocol. This is a retrospective review of all adult patients who required at least 24 h of Impella ® support and received a heparin-based purge solution. In total, 109 patients were included in the final analysis. The most common indication for Impella ® device insertion was cardiogenic shock (76%) with the remaining patients receiving a device for a high-risk procedures; typically coronary artery bypass grafting or percutaneous coronary intervention. A total of 9 thrombotic events occurred among 8 (7%) patients and 50 bleeding events occurred among 43 (39%) patients, with the most common classification being BARC 3a (60%). A univariate analysis revealed that patients were more likely to bleed if they were less than 65 years old, had an indication of cardiogenic shock for Impella ®, inserted the device peripherally, were on dual antiplatelet therapy, or had an intra-aortic balloon pump prior to Impella ® insertion, the latter of which was confirmed with a multivariate analysis (OR 2.5 [1.072–5.830]; p = 0.034). For those monitored by anti-Xa, the presence of two or more values greater than 0.40 IU/mL was a risk factor for bleeding ( p = 0.037). Our study identifies risk factors for bleeding in patients receiving temporary MCS with an Impella ® .